18F-FDG PET/CT and 99mTc-MIBI SPECT/CT Findings in a Patient With Eosinophilic Solid and Cystic Renal Cell Carcinoma. (25th May 2022) - Tong, Zhenghao; Shen, Qi; Sun, Hongwei; Zhang, Jianhua; Fan, Yan
Abstract: A 26-year-old woman was incidentally discovered to have bilateral renal tumors on ultrasound, and percutaneous biopsy of the right kidney lesion proved eosinophilic solid and cystic renal cell carcinoma. 18 F-FDG PET/CT demonstrated hyperdense or isodense lesions on CT without FDG uptake, whereas 99m Tc-MIBI SPECT/CT fusion images showed tumors with increased 99m Tc-MIBI uptake. This case indicates that the 99m Tc-MIBI SPECT/CT is a potential method for the differentiation of renal tumor with eosinophilic features from other renal tumor histology.